1999
DOI: 10.1007/s000110050442
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with polymyxin B-immobilized fiber reduces platelet activation in septic shock patients: Decrease in plasma levels of soluble P-selectin, platelet factor 4 and β-thromboglobulin

Abstract: Our findings suggest that soluble P-selectin, PF-4 and betaTG may be associated with septic shock and that PMX-F is effective in reducing these markers in patients with septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 23 publications
3
47
0
Order By: Relevance
“…An antagonistic effect of PmxB on endotoxic activities of such Ara4N-containing LPSs in relation to interaction between PmxB and the LPSs has not been investigated in detail, but such investigations, like the present study, are necessary to obtain useful information for treatment of infections by bacteria containing such LPSs. Recently, PmxBimmobilized fiber was developed for clinical application in hemoperfusion to eliminate blood endotoxin in septic shock patients (2,21). Based on the information obtained in the present study, PmxB-immobilized fiber is expected to be effective for elimination of B. cepacia LPS, but soluble PmxB is not expected to be effective in suppressing endotoxic activity.…”
Section: Discussionmentioning
confidence: 75%
“…An antagonistic effect of PmxB on endotoxic activities of such Ara4N-containing LPSs in relation to interaction between PmxB and the LPSs has not been investigated in detail, but such investigations, like the present study, are necessary to obtain useful information for treatment of infections by bacteria containing such LPSs. Recently, PmxBimmobilized fiber was developed for clinical application in hemoperfusion to eliminate blood endotoxin in septic shock patients (2,21). Based on the information obtained in the present study, PmxB-immobilized fiber is expected to be effective for elimination of B. cepacia LPS, but soluble PmxB is not expected to be effective in suppressing endotoxic activity.…”
Section: Discussionmentioning
confidence: 75%
“…Apheresis, which is a selective adsorption technique, can lower the levels of toxins and cytokines in the blood. We and other investigators have reported that polymyxin B-immobilized fiber (PMX-F) therapy is effective in reducing the levels of various cytokines in gram-negative sepsis patients [8, 10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…Ten patients were treated with PMX-F (Toraymyxin ® , Toray Medical Co., Ltd, Tokyo, Japan) (group A), and conventional treatment was continued in the other 10 patients (group B). PMX-F and the hemoperfusion column have been described previously [8, 9, 10, 11]. To reduce the toxic effect of polymyxin B and derive benefit from the lipopolysaccharide blocking property, polymyxin B was immobilized onto insoluble fibers creating a hemoperfusion column to use as an extracorporeal endotoxin removal device for the treatment of sepsis [8, 9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Summary of the main randomised trials assessing influence of PMX on mortality of patients with severe sepsis or septic shock. Only Payen et al's study was considered at low risk of bias [13][14][15][16][17] as prescribed in this population, does not likely portend meaningful survival advantage. Secondly, the ABDOMIX trial did not identify patients with the highest likelihood of deriving benefit from PMX therapy by screening patients for elevated circulating levels of endotoxin.…”
mentioning
confidence: 95%